Discrepancies Between the Management of Fever in Young Infants Admitted From Urban General Emergency Departments and Pediatric Emergency Departments. Issue 8 (4th August 2022) - Jain, Priya Narayanan; Lerer, Rikah; Choi, Jaeun; Dunbar, Julie; Eisenberg, Ruth; Hametz, Patricia; Nassau, Stacy; Katyal, Chhavi
Abstract : Introduction/Objective: Most pediatric emergency visits occur in general emergency departments (GED). Our study aims to assess whether medical decision making regarding the management of febrile infants differs in GEDs from pediatric EDs (PED) and deviates from pediatric expert consensus. Methods: We conducted a retrospective chart review on patients younger than 60 days with fever admitted from 13 GEDs versus 1 PED to a children's hospital over a 3-year period. Adherence to consensus guidelines was measured by frequency of performing critical components of initial management, including blood culture, urine culture, attempted lumbar puncture, and antibiotic administration (<29 days old), or complete blood count and/or C-reactive protein, blood culture, and urine culture (29–60 days old). Additional outcomes included lumbar puncture, collecting urine specimens via catheterization, and timing of antibiotics. Results: A total of 176 patient charts were included. Sixty-four (36%) patients were younger than 29 days, and 112 (64%) were 29 to 60 days old. Eighty-eight (50%) patients were admitted from GEDs. In infants younger than 29 days managed in the GEDs (n = 32), 65.6% (n = 21) of patients underwent all 4 critical items compared with 96.9% (n = 31, P = 0.003) in the PED. In infants 29 to 60 days old managed in GEDs (n = 56), 64.3% (n = 36) patients underwent all 3 critical items compared with 91.1% (n = 51, P < 0.001) in the PED. Conclusions: This retrospective study suggests that providers managing young infants with fever in 13 GEDs differ significantly from providers in the PED examined and literature consensus. Inconsistent testing and treatment practices may put young infants at risk for undetected bacterial infection.